Assessment of Nitrogen Volatilization and Greenhouse Gas Emissions from Urea with N-stabilizer in a Productive Oil Palm Plantation (Elaeis guineensis Jacq.) - Waraqi, Bismo; Agusta, Herdhata Herdhata; Sudradjat; Hariyadi (Department of Agronomy and Horticulture, IPB University, 2024)
Nitrogen fertilization plays a crucial role in supporting plant growth. However, nitrogen in the soil can be lost through rainwater leaching. To address this issue, the concept of fertilizing N-stabilizer-coated urea was proposed. The aim is to reduce nitrogen loss on the field due to vaporization and minimize greenhouse gas (GHG) emissions. The study was conducted to assess the effectiveness of this N-stabilizer-coated urea in reducing nitrogen loss through vaporization, improving GHG emissions, and its impact on plant growth and leaf quality. The research was conducted at IPB-Cargill Jonggol, Bogor, West Java, oil palm education and research station from August 2021 to March 2022. The experimental design employed a completely randomized block design. The fertilizer treatments included four types of nitrogen fertilizers: urea (46% N), coated urea with N-stabilizer (46% N), ZA (21% N), and NPK (15-15-15, 15% N). Additionally, a control treatment without any fertilizer application was included. All treatments were replicated three times. Data analysis was done using the SAS (Statistical Analysis System) 9.0 program. The F-test was conducted, followed by DMRT (Duncan Multiple Range Test) advanced tests at a 5% error level. The results revealed that urea with N-stabilizer fertilization significantly reduced NH3-vaporization by 53% in the first week compared to the application of normal urea. NH3-vaporization level from ZA and NPK was < 1% compared to urea application. Field application of urea with N-stabilizer showed no significant difference in greenhouse gas emission (GHG) compared to the other nitrogen fertilizer types. The GHG values ranged from 7.10 to 7.29 g CO2-e.m-2 per day. The use of N-stabilizer-coated urea could be an effective approach to minimize nitrogen loss through vaporization and reduce greenhouse gas emissions while maintaining comparable results to other nitrogen fertilizer types in terms of GHG emissions on the field.